Doing business model innovation for sustainability transitions — Bringing in strategic foresight and human centred design. (August 2022) - Hall, Stephen; Workman, Mark; Hardy, Jeffrey; Mazur, Christoph; Anable, Jillian; Powell, Mark; Wagner, Sophie Marie
Abstract: This paper brings together socio-technical transitions theory with strategic foresight and human centred design. The aim is to bring in new methods for analysing the business model element of sustainability transitions. We propose a process for doing business model innovation work. Business models have become a key area of focus, particularly in the energy sector. Recent work shows how the development of new business models co-evolves with elements of the energy system, either driving technological innovation, changing user practices or placing pressure on the institutional or policy regime. At the same time, there is no recognised process for business model research aimed at transition management. It is time therefore to propose a more formalised and theoretically grounded approach to business model innovation work. We use this contribution to synthesise the lessons of a four-year research project centred on energy utility business models with industrial, commercial and government stakeholders. We describe the process adopted, and insights this process generated. We seek to establish this process in the literature, invite others to utilise it, adapt it and critique it.